Mathematical Modeling and Calculation of Volcanic Ash Dispersion from Mount Lewotobi Using the Gaussian Plume Approach - Ivone Lovenia Youvita; Naufal Ridho Maliki; Dian Candra Rini Novitasari (Indonesian Journal of Mathematics and Natural Sciences, 2025)
The eruption of Mount Lewotobi at the end of 2024 and throughout 2025 caused widespread volcanic ash dispersion and had a significant impact on the socio-economic aspects of the community, including mass evacuations, damage to settlements, transportation disruptions, and airport closures. These problems required scientific modeling that could accurately describe the pattern of ash dispersion. This study uses a quantitative approach through mathematical modeling based on advection equations, the law of mass conservation, and the Gaussian Plume model simulated using MATLAB software. The purpose of this study is to develop a mathematical model to map the direction and pattern of volcanic ash dispersion as a basis for disaster mitigation planning. The simulation results show that volcanic ash tends to spread westward and northwestward following the dominant wind patterns, forming an asymmetrical plume. These findings confirm that mathematical modeling and computer simulation can improve the accuracy of predictions and support the effectiveness of technology-based disaster mitigation strategies.